Law Enforcement of Narcotics Cases in Anti Lodaya Operations by Kuningan Police - Mulya, Agres Setia; Saefudin, Yusuf (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Drug abuse in Indonesia has become a serious problem that threatens the younger generation and the welfare of society. Narcotics, which come from plants or synthetics, have the potential to cause dependence and extensive negative impacts, both socially, economically and culturally. This research aims to analyze law enforcement against narcotics cases through Operation Antik Lodaya by Kuningan Police, which is a systematic effort in eradicating drug trafficking. The research method used is empirical juridical with descriptive analytical approach, relying on primary data from interviews and observations. The results show that Operation Antik Lodaya does not only focus on law enforcement, but also includes prevention and rehabilitation efforts for drug abuse. Despite this, the operation faced various obstacles, including organized crime networks and the risk of information leaks. Effective law enforcement requires synergy between law enforcement officials, the government, and the community to create a safe and drug-free environment. This research is expected to contribute in formulating more effective strategies in handling narcotics cases in Kuningan and surrounding areas.